Data conversion from the OWL data format to the XML TODOS format while saving the logical and structural information content - Huraliuk, A.; Rostoka, M. (Problems of Engineer-Pedagogical Education, 2020)
With the introduction of the Semantic Web and semantic technologies, ontologies have emerged and become one of the most prominent paradigms for representing knowledge. The ontologization of the knowledge presented in it is considered the basis for the further development of the Semantic Web. Ontology is an attempt of comprehensive and detailed formalization of a certain field of knowledge using a conceptual scheme. Typically, such a scheme consists of a data structure containing all relevant classes of objects, their relationships and regulations (theorems, restrictions) adopted in this area. One of the most commonly used languages for describing web ontologies in the world practice is OWL (Web Ontology Language), which is designed to provide tools that can be used to describe classes and the relationships between them that are common to web documents and applications. However, there are a number of tasks for which the use of the OWL language is impractical. The domestic development of TODOS (Transdisciplinary Ontological Dialogues of Object-Oriented Systems) was created to solve some of these problems using a language created on the basis of the XML data presentation standard. The relevance of the article is conditioned by the insufficient development of the relationship between various software tools designed to create, describe, visualize and edit ontologies; namely by the absence of applications that would ensure the conversion of data from the OWL format to the TODOS system format and vice versa. This article describes a method for two-way data conversion between the OWL and the TODOS system language formats. The analysis of the basic constructions of the OWL and XML (TODOS) languages is carried out. The issues of functional equivalence of the convertible and original systems are considered. The problems are identified with the preservation of the main logical and structural content of information associated with different power languages, etc. Authoring is proposed (a java language software application) for implementing the conversion of the mentioned data formats. As a result of the research, outlined schematically in the present article, it is concluded that it is impossible to establish complete mutual correspondence between the OWL and XML (TODOS) languages. Despite the fact that OWL is a more powerful semantic system, according to some of the visualization capabilities of XML, TODOS exceeds OWL, and, accordingly, the equivalence function of the transformation of basic constructions of specified languages does not have the transitivity property. However, with certain assumptions, a partial conversion model can be created where data loss would be minimal.